Фауна рептилий (Reptilia) Северо-Восточного Прикаспия - Неручев, В.В.; Васильев, Н.Ф. (Вестник зоологии, 1978)
Data collected for 1962-1976 are presented on the landscape-territorial distribution of 27 reptile species in the North-Eastern Caspian area. Heterogeneity of the fauna is marked. It is represented by elements from different zonal complexes; herpetoiauna is analyzed according to the zonal character and ways of its formation under the effect of quaternary transgressions of the Caspian Sea are considered.